Exercise stress global longitudinal strain echocardiography can detect subclinical cardiac dysfunction and assist in risk stratification in children with Kawasaki disease: a 3-year follow-up study. (25th November 2020) - Chen, W; Wang, Y; Song, W.J; Yi, W.F; Qi, T.F; Ma, X.J; Liu, L.P; Gu, Y; Zhao, Y; Sun, Y
Abstract: Background: Global longitudinal strain (GLS) echo has been regarded as a sensitive and reproducible indicator for detection of subclinical cardiac dysfunction in children with Kawasaki disease (KD), but whether it can assist in differentiating KD patients with different severity of coronary artery lesions (CALs) has been rarely reported. The purpose of this study was to determine the feasibility of GLS derived from rest and exercise stress echo in risk stratification in patients with KD. Methods: 43 children with KD and 50 healthy controls were enrolled. KDs was divided into 3 groups according to the severity of CALs based on Z score, which was measured at the 3-year follow-up, G1 = KD without CALs (Z<2), G2 = KD with mild CALs (2≤Z<5), G3 = KD with severe CALs (Z≥5). Both group underwent echo at the onset of KD diagnosis and at the 3 years' follow-up, including: diameter of LA and LV, thickness of LVPW and IVS, LVFS, LVEF, and rest GLS (GLSrest). Both group also accomplished the exercise stress echo at the 3 years' follow-up, who squatted quickly to reach target heart rate and stress GLS (GLSstress) was recorded. Patients in G3 underwent a CMR examination, including LGE, to detect myocardial ischemia or infarction. Results: 38 KDs and 50 HCs had normal exercise tolerance. There were 18, 8, and 12 patients in G1, G2, and G3, respectively. LA, LV, LVPW, IVS and LVEF, were not significantly different in the KDs at the onset and 3-year follow-up, and so did that between KDs and HCs (all p>0.05). Both GLSrest and GLSstress in the KDs were significantly decreased compared with HCs (GLSrest: −17.2±9.1% vs. −22.3±0.7%, p<0.01; GLSstress: −20.7±3.5% vs. −27.7±0.7%, p<0.01, seen in Fig.1A, B). However, there were no significant difference in GLSrest among 3 subgroups of KDs (G1: −18.0±10.0%; G2: −19.7±1.2%; G3: 14.4±10.4%; all p>0.05, seen in Fig.1C). GLSstress in the G3 decreased significantly compared with that in G1 and G2 (G3 vs. G1: −16.8±2.6% vs. −22.8±1.9%, p<0.01; G3 vs. G2: −16.8±2.6% vs. −22.1±2.5%, p<0.01, seen in Fig. 1D). GLSrest had no correlation with Z score (r=0.08, p=0.62), but GLSstress correlated well with Z score (r=0.70, p<0.01). 8 of 12 (67%) patients in the G3 underwent CMR and 6 of 8 (75%) were found endomyocardial enhancement on LGE, which indicated myocardial infarction corresponding to the territory of abnormal coronary arteries (seen in Fig. 2). Conclusions: GLS derived from rest and exercise stress speckle-tracking echo can detect subclinical cardiac dysfunction in KD patients with normal LV systolic function by conventional measurements, but rest GLS could not assist in differentiating KD patients with different severity of CALs. Exercise stress GLS, which correlated well with Z score, has the potential in risk stratification in children with KD, and thus may provide prognostic value in multidisciplinary treatment strategy. Funding Acknowledgement: Type of funding source: None